Data Center Energy and Cost Saving Evaluation. (August 2015) - Song, Z.; Zhang, X.; Eriksson, C.
Abstract: In data centers, about 40% of the total energy is consumed for cooling the IT equipment. Cooling costs are thus one of the major contributors to the total electricity bill of large data centers. This paper studies two factors affecting data center cooling energy consumption, namely air flow management and data center location selection. A unique rack layout with a vertically cooling air flow is proposed. Two cooling systems, computer room air conditioning (CRAC) cooling system and airside economizer (ASE), have been studied. Based on these two cooling systems, four cities have been selected from the worldwide data center locations. A number of energy efficiency metrics are explored for data center cooling, such as power usage effectiveness (PUE), coefficient of performance (COP) and chiller hours. By analyzing the effects of chiller hours and economizer hours, comparative economic results of cooling power consumption are provided in both systems. The results show that the cooling efficiency and operating costs vary significantly with different climate conditions, energy prices and cooling technologies. As climate condition is the major factor which affects the airside economizer, employing the airside economizer in the cold climate yields much lower energy consumption and operation costs.